Localisation Of The Ramayana Epic In Malaysian Visual Arts - Chelliah Thiruchelvam, Cheryl (2021)
This research examines the continued presence of elements and derivatives from the Ramayana epic that are still prevalent in Malaysian visual arts despite the introduction of the NCP. Using New Art History as a conceptual framework, this research examines and analyses selected local artworks that have been produced by artists since independence (1957) to this day across various mediums through the lens of wayang kulit.